LEXICOGRAPHY: HISTORICAL DEVELOPMENT AND PROBLEMS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Lexicography is the practice of compiling, writing, and editing dictionaries. It involves a detailed study of words, their meanings, and their usage in various contexts. This article explores the field of English lexicography, discussing its historical development, key methodologies, and the challenges faced by lexicographers. It also examines how digital advancements have transformed the process and the role of lexicography in contemporary society.